KAMPUNG KERBAU BANYUBIRU: PERSPEKTIF BUDAYA DAN SIMBOL KEKAYAAN - Hikmawati, Hanifah (Institut Agama Islam Ngawi, 2024)
Abstract: Buffalo is a strong and large animal that is mostly bred by the people of Bulak Pepe hamlet, Banyubiru village. The motivation for buffalo farming in the village, apart from being inherited from generation to generation, is also based on a system of saving wealth in the form of livestock that can be bred. Hundreds of buffalo support the community's economy in which there are also values ​​and norms from customs and traditions that make Bulak Pepe hamlet a cultural village. he formulation of the problem in this research is, first, how are efforts to strengthen the Banyubiru buffalo village community as a symbol of wealth? second, how did the Banyubiru buffalo village become a cultural entity? The research method used is descriptive qualitative. The researcher served as the key instrument, sampling data sources purposively and snowballing, collecting techniques using data triangulation, and data analysis were inductive/qualitative, and the emphasis on the results was more on meaning than generalization. The theory used is the concept of habitus as the truth of symbolic domination which was initiated by Pierre Bourdieu. The results of this research are that the people of Bulak Pepe term the buffalo as a 'raja kaya' animal, meaning that the animal is treated as a king, manifesting as a symbol of wealth, namely the buffalo has a high selling value, its existence can be a symbol of wealth for the people of Bulak Pepe village, Banyubiru village. Traditions of cultural entities can attract tourists so that they can have an impact on the community's economy, including many buffalo buyers who come from the Ngawi area or outside Ngawi who are ready to buy their livestock. Keywords: Buffalo, Culture, Symbol of Wealth, Banyubiru village